From the Hague to Jakarta:: Changes in Thai Foreign Policy towards the Netherlands in 1949 - Preeyanont, Thanat (Journal of Letters, 2020)
In 1945, a few days after the Japanese Imperial Army had surrendered, the indigenous people on the Indonesian archipelago established the Republic of Indonesia and declared independence from their colonizers, the Dutch. The events led to a 4-year conflict including physical war and negotiations, before the Dutch government finally transferred its sovereignty over the archipelago to the indigenous government in 1949. Through historical diplomatic correspondence from both Thai and Dutch archives, this article examines changes in Thai foreign policy towards the Netherlands in the last year of the conflict. Between 1945-1949 the Thai government almost always recognized Dutch sovereignty over the Indonesian archipelago, however, in December 1949, the Thai government abandoned its former policy and recognized the de facto sovereignty of the Republic of Indonesia. This article argues that the Thai government decided to shift its policy because late negotiation between the Netherlands and the Republic of Indonesia became more beneficial to the latter and the US government also began to show support of the indigenous cause.